Efficacy and safety of single-dose ivermectin in mild-to-moderate COVID-19: the double-blind, randomized, placebo-controlled CORVETTE-01 trial - Wada, Tatsuhiko; Hibino, Makoto; Aono, Hiromi; Kyoda, Shunsuke; Iwadate, Yosuke; Shishido, Eri; Ikeda, Keisuke; Kinoshita, Nana; Matsuda, Yasuki; Otani, Sakiko; Kameda, Ryo; Matoba, Kenta; et al. (Frontiers in Medicine, 2023)
Background To investigate whether ivermectin inhibits SARS-CoV-2 proliferation in patients with mild-to-moderate COVID-19 using time to a negative COVID-19 reverse transcription-polymerase chain reaction (RT-PCR) test. Methods CORVETTE-01 was a double-blind, randomized, placebo-controlled study (August 2020–October 2021) conducted in Japan. Overall, 248 patients diagnosed with COVID-19 using RT-PCR were assessed for eligibility. A single oral dose of ivermectin (200 μg/kg) or placebo was administered under fasting. The primary outcome was time to a negative COVID-19 RT-PCR test result for SARS-CoV-2 nucleic acid, assessed using stratified log-rank test and Cox regression models. Results Overall, 112 and 109 patients were randomized to ivermectin and placebo, respectively; 106 patients from each group were included in the full analysis set (male [%], mean age: 68.9%, 47.9 years [ivermectin]; 62.3%, 47.5 years [placebo]). No significant difference was observed in the occurrence of negative RT-PCR tests between the groups (hazard ratio, 0.96; 95% confidence interval [CI] 0.70–1.32; p = 0.785). Median (95% CI) time to a negative RT-PCR test was 14.0 (13.0–16.0) and 14.0 (12.0–16.0) days for ivermectin and placebo, respectively; 82.1% and 84% of patients achieved negative RT-PCR tests, respectively. Conclusion In patients with COVID-19, single-dose ivermectin was ineffective in decreasing the time to a negative RT-PCR test. Clinical Trial Registration ClinicalTrials.gov, NCT04703205.